Effects of particle loading, temperature and surface treatment on moisture absorption of CFB fly ash reinforced thermoset composite - Onishi, Sakura E. (College of Engineering, University of the Philippines Diliman, 2014)
Coal combustion is widely used in the Philippines and is a major contributor to power generation due to its low cost; however, it produces wastes such as emissions and fly ash (FA). Traditional fuel combustion uses pulverized coal (PC) boilers whiles modern technology involves the use of circulated fluidized bed (CFB) boilers which produces less emissions and are more efficient. However, the fly ash produced from CFB combustion has limited application to the construction industry as opposed to PC FA which is used as an additive to the cement industry. In this study, CFB FA is used as filter and the matrix is orthophthalic unsaturated polyester resin. Moisture absorption study is conducted on the composite by immersing in water and constant weighing of samples at specified time intervals. Percent weight gain is reported. Particle loading (0%, 10%, 30%, 40%) and sorption temperatures (30°C, 50°C, 80°C) are varied and their effects are observed. With the increase in particle loading, absorbed moisture increases while diffusivity decreases. Increase in temperature leads to an increase in moisture absorption and diffusivity. The CFB FA is also treated using coconut oil which is composed of saturated fatty acids (majority of which is lauric oil). Coconut oil serves as a non-coupling type surface modifier. Untreated and treated fly ash samples are characterized by X-ray Flourescence (XRF), Scanning Electron Microscopy (SEM) and Fourier Transform Infrared Spectroscopy (FTIR). The effect of treatment to composite moisture absorption at 80°C (different particle loading) is observed and it is found to decrease moisture absorption.